Lamotrigine treatment of bipolar disorder: data from the first 500 patients in STEP-BD. - Marangell, L; Martinez, J; Ketter, T; Bowden, C; Goldberg, J; Calabrese, JR; Miyahara, S; Miklowitz, D; Sachs, G; Thase, M (2004)
OBJECTIVE: To describe the frequency and correlates of lamotrigine therapy among the first 500 patients enrolled into the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) study. METHOD: Systematic recording of psychiatric history and medication data at intake into the STEP-BD project. RESULTS: Of the participants with bipolar disorder type I or II (n = 483), 77 (15.4%) were currently taking lamotrigine (mean dose: 258.12 mg/day) and 52 (10.4%) reported prior lamotrigine use. The groups were comparable with regard to duration of illness and mood state at study entry. Compared with participants who had never taken lamotrigine, those currently treated with lamotrigine were significantly more likely to have a prior history of rapid cycling (62.5% vs. 43.1%; p < 0.01) and an antidepressant-induced switch to (hypo)mania (49.3% vs. 33.3%; p < 0.01). In contrast, only 16.9% of lamotrigine-treated participants were taking an antidepressant at study intake, as compared with 29.1% of participants with no history of lamotrigine therapy (p < 0.03). CONCLUSIONS: While noting the limitations of a cross-sectional assessment, these data suggest that lamotrigine therapy was commonly used in these academic centers for patients with bipolar disorder several years before it was recommended in the American Psychiatric Association practice guidelines, particularly in patients with a history of rapid cycling or antidepressant-induced mania.